Acute and Chronic Catabolic Responses to CrossFit(®) and Resistance Training in Young Males - Faelli, Emanuela (Int J Environ Res Public Health, 2020)
Given the wide variety of conditioning program trainings employed, the present study compared the catabolic effects induced by CrossFit(®) and resistance training in moderately trained subjects. Twenty males joined either the CrossFit(®) group (n = 10; 30 min/day of “workout of the day”) or the resistance training (RT) group (n = 10; 30 min/day of resistance exercises) thrice a week, for 8 weeks. Salivary levels of cortisol, interleukin 1-beta (IL-1β), and uric acid were assessed via enzyme-linked immunosorbent assays before (PRE) and 30-min after (POST) SESSION 1 and SESSION 24. Variables’ percentual changes were computed as (POST-PRE)/PRE*100 in each session (Δ%). CrossFit(®) acutely increased cortisol levels in both sessions, with a significant decrease in Δ%cortisol from SESSION 1 to 24. In the RT group, cortisol values decreased in both sessions, only acutely. A significant decrease in IL-1β levels was registered acutely in both groups, in both sessions, whereas Δ%IL-1β was not different between the two groups. While uric acid levels increased in both groups acutely, a chronic downregulation of Δ%uric acid, from SESSION 1 to 24, was appreciated for the RT group only. Overall, CrossFit(®) appeared to induce more intense effects than the RT program as to the investigated catabolic responses.